Penerapan Metode Harga Pokok Pesanan dalam Perhitungan Biaya Kegiatan Organisasi Mahasiswa: Studi Kasus pada Himpunan Mahasiswa Manajemen Universitas Bina Sarana Informatika - Firman Achmad N; M Rifky Habibi; Vio Vie Tarisha; Bagas Pangestu; Bagas Surya (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to apply the job order costing method in calculating the cost of the "Sharing Takjil and Breaking Fast Together" activity organized by the UBSI Management Student Association in March 2025. This activity is the object of study because it has project-based cost characteristics with elements of membership fees and donations. With a quantitative descriptive approach, data was obtained from the committee's official financial report and calculated based on the classification of direct and indirect costs. The results show that most of the costs are allocated for consumption (±86%) and the rest for equipment (±14%). With a total expenditure of IDR1,075,950 and an estimated number of 34 participants, the cost per participant is IDR31,645. The application of this method not only increases financial transparency, but also provides a rational basis for planning future organizational activities, and provides an understanding that the job order costing method is not only useful for the manufacturing sector, but also for non-profit entities in making activity-based financial decisions.